Coronary balloon angioplasty, stents, and scaffolds. Issue 10096 (19th August 2017) - Byrne, Robert A; Stone, Gregg W; Ormiston, John; Kastrati, Adnan
Summary: Since the first coronary angioplasty on Sept 16, 1977, the field of percutaneous coronary intervention has evolved rapidly. Now marking its 40th anniversary, percutaneous coronary intervention has become one of the most common medical procedures worldwide. Much of this progress has been due to the iteration and improvement of angioplasty technologies. Balloon angioplasty was limited by unpredictable procedural outcomes due to vessel dissection and recoil, and a high rate of restenosis. The introduction of stents resulted in more stable early results and lower rates of restenosis, although early stent thrombosis and neointimal hyperplasia causing vessel renarrowing were key limitations. Drug-eluting stents delivering antiproliferative agents significantly lowered the rates of restenosis, permitting widespread use of percutaneous coronary intervention in more advanced and complex disease. Although fully bioresorbable scaffolds have the potential to further improve long-term outcomes, they have not yet achieved results equivalent to those of conventional metallic drug-eluting stents in the early years after implantation. Progress in catheter technology did not occur in isolation, and the success of percutaneous coronary intervention is also due to important advances in intracoronary imaging, and adjunct pharmacotherapy—each of which is reviewed in other papers in this Series.